The Evaluation of Public Awareness Regarding Early Signs of Stroke and Heart Attack Emergencies: Evaluation of Public Awareness Regarding Early Signs of Stroke and Heart Attack Emergencies - Hardianti, Siti (JURNAL KESMAS DAN GIZI (JKG), 2024)
Stroke and heart attack are leading causes of morbidity and mortality worldwide. Early detection of emergency signs in both conditions is critical to increase the chances of recovery and reduce the risk of fatal complications. This study aims to evaluate the level of public awareness of the early signs of stroke and heart attack, and the factors that influence this understanding. The research method used was a quantitative survey with questionnaires distributed to respondents from various backgrounds of age, education, and occupation. The results showed that there is still a significant knowledge gap among the public regarding typical stroke symptoms, such as sudden weakness on one side of the body, speech impairment, and loss of balance, as well as heart attack symptoms, such as chest pain, shortness of breath, and cold sweat. Factors such as education level, access to health information, and personal or family experience with cardiovascular disease influence the level of awareness of respondents. Therefore, wider education efforts through health campaigns, social media, and community training are needed to improve early detection and rapid response to these emergencies. With increased public awareness, it is hoped that mortality and complications from stroke and heart attack can be minimized.